Benedicks' theorem for the Weyl Transform associated with the Heisenberg group. Issue 6 (3rd June 2018) - Patra, Partha Sarathi; C, Sivaramakrishnan; Naidu D, Venku
ABSTRACT: In this article, we discuss Benedicks' theorem for the Weyl transform associated with the Heisenberg group. Supposeσ ∈ L 2 ( H n × R, S 2, d ν × d μ ) be a function with compact support and if the Weyl transformW σ is of finite rank, then we show that σ is zero almost everywhere onH n × R .